Increasing RPL-based LLN lifespan using harvested solar energy - Basalooml, Abdullah Ahmed S.; Habaebi, Mohamed Hadi; Khan, Sheroz; Shaikh, Faraz Ahmed (IEEE, 2019)
Internet of Things (IoT) tends to be the next nd expects to deployed small co devices wherever and whenever, and thus such devices often are constrained in processor, memory, and energy. These devices known as sensor nodes which connected with each other to form a network of different nodes. As a matter of fact, routing the data in such environment was a challenge because of constrained sources of power therefore, Routing Protocol for Low-Power and Lossy Network (RPL) was formed by Internet Engineering Task Force (IETF) to develop an adapted routing solution for such networks that contain large number of constrained nodes with limited processing, power, and memory. This paper proposes a solar energy harvesting module to power such constrained network devices while RPL routing protocol in used and, thus studying the effect on prolonging network lifetime. In addition, simulation is conducted in three different scenarios by using Contiki Cooja, furthermore, we evaluated battery-powered and energy harvesting-powered nodes to study and present the effects in extending RPL network lifetime. Consequently, the results showed that, the network with no-energy harvesting operated for around 4:08:04 with a dramatically decrease of connection between all the nodes, while the network with energy harvesting operated for around 6:40:01. Therefore, energy harvesting module provided a total extended network lifetime is 2:31:97(two hours and thirty-one minutes and ninety-seven seconds). Furthermore, in term of RPL metrics evaluation, OF0 outperform ETX in term of throughput, pack ry ratio, energy consumption, and network connectivity.